The 1, 2-ethylenediamine SQ109 protects against tuberculosis by promoting M1 macrophage polarization through the p38 MAPK pathway - Mona Singh; Santosh Kumar; Baldeep Singh; Preeti Jain; Anjna Kumari; Isha Pahuja; Shivam Chaturvedi; Durbaka Vijay Raghava Prasad; Ved Prakash Dwivedi; Gobardhan Das (Communications Biology, 2022)
The adamantine derivative SQ109 induces protective pro-inflammatory cytokines and promotes Th1 and Th17-immune responses that inhibit bacterial burden in a tuberculosis mouse model.